2022
DOI: 10.1186/s12959-022-00376-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factor of post-operative lower extremities deep vein thrombosis in patients undergoing gynecologic surgery: a single-institute cross-sectional study

Abstract: Background and aim The study of prevalence and risk factors of postoperative lower limb deep vein thrombosis (DVT) in Thai gynecologic patients was limited. The present study was conducted to evaluate this issue. Methods The patients were age > 15 years old without a history of DVT or pulmonary emboli (PE) scheduled for laparotomy or vaginal gynecologic surgery between May and November 2020 were invited to participate. All of these patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In our study, age had a positive predictive value for postoperative DVT in cervical cancer patients. This is in line with the results of Lorchaivej et al 26 This might be because vascular sclerosis, increased blood viscosity, and dysfunctional venous valves are common in seniors. 28 Also, it has been discovered that patients’ vascular endothelial cells produce more procoagulant compounds and fewer anticoagulant substances with the increase of age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, age had a positive predictive value for postoperative DVT in cervical cancer patients. This is in line with the results of Lorchaivej et al 26 This might be because vascular sclerosis, increased blood viscosity, and dysfunctional venous valves are common in seniors. 28 Also, it has been discovered that patients’ vascular endothelial cells produce more procoagulant compounds and fewer anticoagulant substances with the increase of age.…”
Section: Discussionsupporting
confidence: 92%
“… 23 25 In this study, individuals with cervical cancer had a postoperative DVT incidence of 24.8%. According to Lorchaivej et al, 26 11.6% of patients with gynecological cancers suffered postoperative DVT. However, retrospective research analyzed 135 gynecological cancer survivors and found that the incidence of DVT in lower limbs was 25.4%.…”
Section: Discussionmentioning
confidence: 98%
“…As surgery-related acute PPI occurs usually within the first 4–6 weeks after surgery and should therefore been assessed within the follow-up of 6 weeks, this possible limitation seems negligible [ 10 ]. As most surgery-associated complications, such as DVT or thromboembolism, occur within the early rehabilitation period (first 7 days [ 19 ]), most of those complications should have been assessed too, as average LOS and therefore clinical control in this study was 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be assumed that most of the sintering as well as intraoperative occult fractures would have been identified during the six week follow-up. As most surgery-associated complications, such as DVT or thromboembolism, occur within the early rehabilitation period (first 7 days [ 35 ]), most of those complications should have been assessed too, as average LOS and therefore clinical control in this study was 7 days. Another limitation might represent the fact that postoperative Hb drop is measured the day after surgery and was not regularly controlled in further follow-up even if some literature demonstrated major Hb drop occurs at day three or four after surgery [ 36 ].…”
Section: Discussionmentioning
confidence: 99%